Guidelines for effective technology facilitation of realistic mathematics education to enhance teaching practice - Laubscher, Dorothy Joy (North-West University (South Africa), 2017)
Different teaching styles and approaches that are employed in a teaching environment have a huge impact on the achievement of learners. The value of using the Realistic Mathematics Education (RME) teaching approach to teaching Mathematics is evident in a number of studies. This study aimed to determine how the RME approach, facilitated by technology, could be used to enhance teaching practice. It also aimed to establish what support needs in-service Mathematics teacherstudents in the South African context had with regard to using the RME approach, and it intended to yield guidelines for the effective use of technology in implementing the RME approach, thereby generating theoretically relevant knowledge to the body of scholarship. A purposeful stratified sample was used to understand what needs in-service Mathematics teachers had in terms of making Mathematics more realistic for their learners. Participants were selected from a group of in-service teachers enrolled for the BEd Honours post-graduate degree in Mathematics education at the NWU. Qualitative design-based research was an appropriate methodology for this study. I produced, evaluated and adjusted content based on the RME approach, presented by means of a mobile application to assist teacher-students in presenting learning content to their learners in a more realistic and relevant way. The first stage of the study consisted of a systematic literature review (SLR) to determine how the RME approach could be facilitated by technology to enhance teaching practice. Individual interviews with participants followed, to determine their needs in terms of effectively implementing the RME approach in their teaching practice. Thereafter iterative cycles of design and intervention took place. A mobile application (app) was used to present content to the participants, based on the needs identified in the individual interviews and the literature review. The re-design of the intervention was guided by testing different versions of the prototype of the app with various users, as well as by literature. Focus group interviews were used to establish the teacher-students’ perceptions and evaluation of the app. The final stage of the study produced guidelines based on the findings of the study. Data were coded, sorted and summarised into themes using a computer assisted qualitative data analysis software (CAQDAS), ATLAS.ti™. The data analysis and interpretation were integrated with the literature review to answer the research questions. Based on these findings, guidelines for the effective use of technology in implementing the RME approach in teaching practice were designed. These guidelines were designed around the five dominant themes in the study, namely Mathematics, RME, ICT, role-players and aspects relating to the app. The guidelines will be of value to teachers, their learners, lecturers, curriculum specialists and instructional designers in the design, implementation and adaptation of mathematical content and course material
PhD (Mathematics Education), North-West University, Potchefstroom Campus, 2017
Keywords: Mathematics education; Realistic mathematics education (RME); mLearning; Mobile app; Systematic literature review (SLR); Qualitative data analysis; Interpretivist; ATLAS.ti™; Teacher-students; Open distance learning (ODL)